Arabic Creative Writing Learning using WSQA (Word, Sentence, Question, & Answer) Method: An Attempt on Quality Upgrading of Labor Demands - Yunus Anis, M (KnE Social Sciences, 2018)
Arabic language has been spoken in the Middle East area since a long time. It is the Lingua Franca in this area. Many particular job markets such as construction or manufacturing and housemaid in Arab world require high-grade quality of employees and workers. One of the solutions to get the quality upgrading of employee and worker is the comprehensive foreign-language training. The employees have to speak and write Arabic language correctly. They are made to practice the language skill using the WSQA method. The WSQA (Word, Sentence, Question, and Answer) is a new model for creative writing. To get the best quality of mastering vocabularies, a beginner of foreign-language learning can use the WSQA model to improve the quality of writing and speaking. This article tries to offer the solution of quality upgrading of labor demands under the language training using the WSQA model, especially for the Indonesian employees or workers who have the great desire to get a particular job in the Arab world. This article will elaborate two basic problems, first about the implementation of WSQA method in basic sentence (nominal sentence) in Arabic language, and the second is the improving of writing skill using WSQA method for the employee and workers as the attempt on quality upgrading of labor demands. Keywords: WSQA method, employee and worker training, Arabic nominal sentence, labor demand, global world